2020
DOI: 10.1016/j.jmb.2020.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Monomer–Dimer Equilibrium of Tubulin with Mass Photometry

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…A dissociation equilibrium constant, K d , of 0.01 nM was calculated from the measured dimer dissociation rate and the estimated dimer association rate . Recent mass photometry measurements reported K d of 3.7 nM . Hence, the expected contribution of tubulin monomers is indeed negligible (about 0.01%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A dissociation equilibrium constant, K d , of 0.01 nM was calculated from the measured dimer dissociation rate and the estimated dimer association rate . Recent mass photometry measurements reported K d of 3.7 nM . Hence, the expected contribution of tubulin monomers is indeed negligible (about 0.01%).…”
Section: Resultsmentioning
confidence: 99%
“…29 Recent mass photometry measurements reported K d of 3.7 nM. 30 Hence, the expected contribution of tubulin monomers is indeed negligible (about 0.01%).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The αβ-heterodimer state is not fixed; rather, purified heterodimers can undergo reversible dissociation with moderately fast kinetics into stable monomers of α- and β-tubulin (Montecinos-Franjola et al, 2016). A wide range of dissociation constants have been reported for purified αβ-heterodimers, from 0.1 nM to 1.0 µM (Mejillano and Himes 1989; Detrich and Williams 1978; Caplow and Fee 2002; Fineberg et al, 2020). This apparent disagreement may be attributable to differences in experimental conditions but also to biologically relevant differences in tubulins.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison by Wu et al of MP with established binding affinity measurement techniques showed that MP binding affinity data of antibody-antigen interactions was in agreement with ITC and BLI measurements and superior in terms of stoichiometry determination. 126 Recently, MP has also been used to quantify binding affinities in the self-association of proteins (FOXP2 oligomerization, 127 tubulin dimerization, 128 CaMKIIα oligomerization 129 ), and for qualitative assessment of affinities between serum haptoglobin protein and hemoglobin 130 and casposase and DNA. 131 Recently, Li et al and Olerinyova et al showed that MP methods can be extended to other classes of biomolecules, such as DNA 132 and membrane proteins.…”
Section: Solution-based Methodsmentioning
confidence: 99%